Blockholder heterogeneity and conflicts in cross-border acquisitions - Chen, Victor Zitian; Hobdari, Bersant; Zhang, Yilei (Journal of Corporate Finance, 2019)
We investigate the principal-principal (PP) conflicts between large blockholders in the context of cross-border acquisitions (CBAs). We focus on the conflicts between family blockholders and two groups of financial institutional investors – banks and mutual funds. We hypothesize that different types of blockholders have heterogeneous preferences with respect to the CBA decision and outcomes. We suggest that the PP conflicts in CBA differ across the blockholders. Banks are pressure sensitive and cooperative with the management because of their clientele relationship with firms, while mutual funds are subject to more financial scrutiny and independent from the management, making them pressure resistant. When in conflict with more powerful family blockholders, mutual funds will choose to exit after a CBA decision, whereas banks are more likely to stay. With an equally distributed voting power, family and mutual fund blockholders will be more motivated to monitor over each other and jointly discipline the management, leading to more careful selection of CBAs and higher overall shareholder value. However, such effects are weak in the case of family and banks. We find support for these conjectures using data on CBAs undertaken by US public firms over the period 2003–2016.